Lithium‐Salt Controlled Electrolyte and Flower‐Like Cobalt Sulfide Cathode for High‐Performance Magnesium Lithium Dual Ion Batteries. Issue 6 (29th April 2021) - Zhang, Xu; Xu, Hao; Yang, Jisheng; Zhu, Yuxiao; Lu, Chong; Zhang, Kemin; Weng, Guoming; Zou, Jianxin
Abstract: Magnesium lithium dual ion batteries (MLIBs) possess the advantages of Mg anodes with low dendrite formation tendency, high volumetric capacity and abundant resources. The fast reaction kinetics of Li + ions for the whole electrochemical redox processes contribute to provide high reversible capacity and long cycle life. In this study, we propose one type of MLIBs coupled with Mg anodes, flower‐like cobalt sulfide (CoS) cathodes, all‐phenyl complex (APC) and lithium chloride dissolved in tetrahydrofuran (THF) derived APC‐ x LiCl/THF ( x =0–0.8 mol L −1 ) electrolytes. By virtue of APC‐0.8 LiCl/THF electrolyte, the capacity of MLIB increases gradually to a high capacity of 507 mAh g −1 at 0.1 A g −1 and maintains a reversible capacity of 219 mAh g −1 at 0.5 A g −1 after 500 cycles. More significantly, Mg 2+ and Li + ions co‐conversion mechanism on the CoS cathodes is demonstrated for MLIBs. The systems studied here may offer insights in the design of MLIBs. Abstract : Mg anodes, three‐dimensional flower‐like cobalt sulfide cathodes, all‐phenyl complex (APC) and lithium chloride dissolved in tetrahydrofuran (THF) derived APC‐0.8 LiCl/THF electrolyte are used for high‐performance magnesium lithium dual ion batteries (MLIBs), demonstrating reversible capacities of 507 mAh g −1 at 0.1 A g −1 and 219 mAh g −1 at 0.5 A g −1 over 500 cycles. Li + /Mg 2+ co‐conversion mechanism is studied by ex‐situ XRD, SEM and HRTEM.